Effectiveness of Homeopathic Medicines as Add-on to Institutional Management Protocol for Acute Encephalitis Syndrome in Children: An Open-Label Randomized Placebo-Controlled Trial - Oberai, Praveen; Varanasi, Roja; Padmanabhan, Maya; Upadhyaya, Alok; Singh, Supriya; Singh, Samarendra Pratap; Vikram, Deepika; Khan, Tariq; Prasad, Ramesh; Gupta, A. K.; Singh, J. R.; Manchanda, Raj K. (Homeopathy, 2018)
Background Acute encephalitis syndrome (AES) is endemic to certain parts of India, with limited treatment options. In our initial exploratory comparative observational study of 151 patients with AES, there was significantly reduced mortality with adjunctive homeopathy compared to institutional management protocol (IMP). The present randomized placebo-controlled trial brings more statistical rigor to this research program.Methods This study was conducted at a pediatric unit from 2013 to 2015. Children aged > 6 months and ≤ 18 years and receiving IMP were randomized to receive adjunctive homeopathy (n = 325) or placebo as control (n = 323). The primary effectiveness analysis was based on Glasgow Outcome Scale (GOS). Morbidity was assessed using the Liverpool Outcome Score for Assessing Children at Follow-up. Analysis was by intention to treat.Results A total of 612 children were analyzed (Homeopathy [H] = 304; Control [C] = 308). The primary outcome, GOS, differed significantly between H and C groups. There was 14.8% death/neuro-vegetative state in the H group compared to 29.8% in the C group. Relative risk was 0.49 (95% confidence interval [CI]: 0.36 to 0.68), with absolute risk reduction of 15.0% (95% CI: 8.6 to 21.6%). Number needed to treat to prevent one additional death/neuro-vegetative state was 6.6 (95% CI: 4.6 to 11.6). Proportional-odds analysis also revealed a greater effect in the H group: odds ratio, 0.40 (95% CI: 0.27 to 0.60). The most frequently used medicines were Belladonna (n = 116), Stramonium (n = 33), Arsenicum album (n = 25), Sulfur (n = 18), Opium (n = 17), and Nux vomica (n = 10).Conclusion Adjunctive homeopathic medicines may improve clinical outcomes associated with AES. Further randomized and controlled studies, using double-blinded trial design, are recommended to discover if the current findings may be corroborated.
Keywords: acute encephalitis syndrome; adjunctive homeopathy; India; Glasgow Outcome Scale